Touchpoint-tailored ultrasensitive piezoresistive pressure sensors with a broad dynamic response range and low detection limit - Chen, Ming (2020)
Wearable pressure sensors with high sensitivity, broad dynamic response range, and low detection limit are highly desirable to enable the applications in electronic skins and soft robotics. In this work, we report a high-performance wearable pressure sensor based on microstructured polydimethylsiloxane (PDMS)/Ag and rough polyimide/Au interdigital electrodes. By tailoring the touchpoints, the resulting pressure sensors show ultrahigh sensitivity (259.32 kPa–1 in the range of 0–2.5 kPa), broad dynamic response range (0–54 kPa), fast response (∼200 μs), and low detection limit (0.36 Pa). Furthermore, the effect of different sensor structural configurations, PDMS geometrical feature, and Ag thickness on the performance of the pressure sensors are systematically investigated. Thanks to these merits, the fabricated pressure sensor is capable of real-time monitoring pulse wave and can act as artificial skin for robot hand to detect weak pressure changes, leading to the great application promise in the fields of biomedical, real-time health monitoring, and intelligent robot.